Teaching of Physics with Physics Suite on the Achievement of Secondary Students. - Akhtar, Salma; Irshadullah, Hafiz M.; Inamullah, Hafiz M.; Tariq, Muhammad (Dialogue (Pakistan))
Teaching of Physics with Physics Suite describes a variety of tools for improving both teaching and learning, including new kinds of homework and exam problems. The major objectives of the study were to examine: (i) the relative effects of teaching Physics with Physics Suite instruction on the academic achievement; (ii) the difference between treatment effects for the students of high and low level of achievement. To achieve the objectives of the study nine null hypotheses were tested. The students of 9 class of the Islamia Collegiate School Peshawar School were selected as sample of the study. Sample students were divided into two groups i.e. experimental group and control group on the basis of previous results by applying pair random sampling. The students of experimental group performed significantly better than control group on the posttest which proved that teaching of physics with the physics suite was more effective than the traditional method of teaching physics. It is recommended that new techniques may be adopted for the promotion of teaching Physics for the best interest of the students.